Design of an Efficient Pumping Scheme for Mid-IR Dy3+:Ga5Ge20Sb10S65PCF Fiber Laser - Stefano Taccheo (IEEE Photonics Technology Letters, 2016)
This letter illustrates the design of a novel medium infrared (Mid-IR) laser based on a photonic crystal fiber made of dysprosium-doped chalcogenide glass, Dy3+:Ga5Ge20Sb10S65. In order to perform a realistic investigation, the simulation is performed by taking into account the spectroscopic parameters measured on the rare earth-doped glass sample. The simulated results show that an optical beam emission close to 4400-nm wavelength can be obtained by employing two pump beams at 2850 nm (pump #1) and 4092 nm (pump #2) wavelengths. As example, for the pump powers of 50 mW (pump #1) and 1 W (pump #2), the input mirror reflectivity of 99%, the output mirror reflectivity of 30%, and the optical cavity length of 50 cm, a signal power close to 350 mW at the wavelength of 4384 nm can be generated. This result indicates that the designed source configuration is feasible for high beam quality Mid-IR light generation and it is efficient enough to find applications in optical free propagation links, optical remote sensing, and medicine.